ENHANCEMENT OF ORGANIZATIONAL COMMITMENT THROUGH STRENGTHENING SHARED LEADERSHIP AND TEACHER SATISFACTION IN FADILAH VOCATIONAL HIGH SCHOOL SOUTH TANGERANG - Jayadih Jayadih; Lisa Chandrasari Desianti; Triningsih Triningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This research aims to determine the effect of shared leadership and job satisfaction on organizational commitment. The subject of the study was Fadilah Vocational High School (SMK Fadilah) teacher of South Tangerang City. A study sample of 36 teachers consist of male and female. The research data was obtained using Likert’s scale instruments to measure organizational commitment variable, shared leadership and teacher job satisfaction. Data analysis using Structural Equation Modeling (SEM) with partial least square (PLS) method. The results of the study proved that there is a positive direct effect of shared leadership variables on job satisfaction and a positive direct effect of job satisfaction variables on organizational commitment. Furthermore, the value of indirect effect of shared leadership variables on organizational commitment variables is greater than the value of direct effect. This means that indirectly the effect of shared leadership variables through job satisfaction variables has a significant effect on changes in organizational commitment variables. This proves that the existence of a job satisfaction mediation variable is full mediation or perfect because its presence results in the relationship between shared leadership variables and previously negative and insignificant organizational commitments turning positive and significant.